Optimalisasi Manajemen Keuangan melalui Pemanfaatan Teknologi Fintech: Studi pada BRI Link ARNAWAMA Klepu - Nazara, Herwian Putri Asih; Hendrajaya, Hendrajaya (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This article aims to analyze the optimization of financial management through the utilization of financial technology (fintech) at BRI Link ARNAWAMA Klepu. The problem focuses on how fintech implementation can improve financial management efficiency, transaction transparency, and accessibility to financial services for the community. To approach this issue, theoretical references from financial management, fintech, and financial inclusion are used. Data were collected through direct observation, interviews with BRI Link agents, and financial transaction documentation, which were analyzed qualitatively. The results show that fintech utilization has improved operational efficiency, reduced financial recording errors, and accelerated transaction processes. Additionally, fintech has contributed to expanding financial service access for communities with limited banking access. This study concludes that the application of fintech in BRI Link ARNAWAMA Klepu’s operations not only optimizes financial management for agents but also promotes increased financial literacy and inclusion in society, creating a more transparent, efficient, and accessible financial system.